FEATURES OF CYTOKINE REGULATION IN PATIENTS WITH MECHANICAL JAUNDICE OF MALIGNANT GENESIS - O. V. Smirnova; V. V. Tsukanov; N. M. Titova; B. G. Gubanov (Медицинская иммунология)
Mechanical jaundice (MJ) of malignant genesis is a clinical syndrome caused by obturation of bile ducts due to malignant tumor growth. It is characterized by specific pigmentation of skin, mucous membranes and sclerae due to increased accumulation of bilirubin in blood serum and other fluids and tissues of the organism. Various immune disorders are detected in patients with mechanical jaundice. Immune reactivity in mechanical jaundice is affected by toxic, infectious, or tumor factors. In connection with these findings, the aim of our study was to measure levels of some pro-inflammatory (IL-2, IL-18, TNFα, IFNγ) and antiinflammatory (IL-4 IL-10) cytokines in patients with malignant disease, depending on serum bilirubin levels. The study included 50 patients with MJ by malignant origin. A control group consisted of 125 practically healthy volunteers comparable with the study group by sex and age. Blood serum cytokine contents in patients and controls was determined by enzyme immunoassay using reagent kits produced by ZAO Vector-Best. Statistical evaluation of data was carried out by means of Statistica for Windows 8.0 and Microsoft Excel software. The levels of IL-2, TNFα, IFNγ and IL-18 were increased before surgery in the patients with mechanical jaundice of malignant genesis, while IL-4 and IL-10 values were reduced in comparison with healthy controls. Altered cytokine regulation in the MJ group manifests as increase in proinflammatory and immunostimulatory cytokine levels, along with decrease in anti-inflammatory cytokine amounts. Predominant feature of immune response may be regarded as prevalence of Th1-immune response when taking into account cytokine levels in blood serum of patients with MJ of malignant genesis. The features of cytokine regulation of patients with malignant MJ depend on the bilirubin content in blood serum. These changes were most frequent in patients with bilirubin level exceeding 60 μmol/L. In general, the quantitative indices of cytokines exhibited unidirectional changes in the groups of MJ patients with different bilirubin levels, except of IL-10. This parameter showed almost 6-fold increase in MJ patients with bilirubin level < 60 μmol/L against control group, and approximately 40 times with respect to the remaining 2 groups. This biological effect may occur due to malignant etiology of the MJ.